Safety culture in handling radioactive materials: a review - Nor Azman, Nor Farah Amirah; Othman, Siti Amira; Abu Bakar, Nurul Fathihah; Jasrin, Nurin Saqinah (2018)
This paper reviews the safety culture in handling radioactive sources. Safety culture refers to how safety is addressed and communicated in the workplace. It encompasses the attitudes, beliefs, perceptions, and values of all employees in an organization in relation to safety. A good safety culture can be promoted by management through commitment to safety, realistic practices for handling hazards, continuous organizational learning and concern for hazards shared across the workforce. The radioactive substances used should comply with the following characteristics where radiotoxicity must be as low as possible, short-living isotopes are preferred than long-living ones and the amounts used must be kept to a minimum. Therefore, the ‘As Low As Reasonably Achievable’ (ALARA) principle was applied that based on the minimization of radiation doses and limiting the release of radioactive materials into the environment by employing all reasonable methods. Besides that, the ALARA principle is an integral part of all activities that involve the use of radiation or radioactive materials and can help prevent unnecessary exposure as well as overexposure. The three major ALARA principles to assist with maintaining doses are time, distance and shielding. It takes a whole team effort to successfully implement the ALARA in safety culture while doing routine element of working in handling radioactive materials.